PENGARUH SIKAP KONSUMEN TERHADAP IKLAN TELEVISI DAN MINAT BELI SUATU PRODUK - Nurtiah Nurtiah; Fatimah Abdillah (Journal of Management Small and Medium Enterprises (SMEs), 2021)
Advertising is a source of product information for consumers. Different responses from consumers to advertisements form various specific attitudes towards an advertisement. Marketers and companies need a positive attitude towards the advertisements produced. So that consumer buying interest is quite strong in the market. This study aims to provide an overview of consumer attitudes towards television advertising on products commonly used by consumers. This study uses primary data obtained directly from distributing questionnaires to 150 respondents, namely the people of Cibungbulang District. The analytical method used is path analysis (path analysis). The results of this research using the path analysis method indicate that companies can still get a positive impact from advertising through television media. Advertising on television is still superior because consumer evaluation of advertising is strong enough to increase purchase interest in products.The results of the study based on path analysis show that consumer attitudes towards television advertising (X) affect consumer attitudes towards brands (2) and purchase interest (Y). If regressed, consumer attitudes towards television advertising (X) have a significant positive effect on attitudes towards brands with a standardized beta value of 0.429 and a significance of 0.000. Attitude towards brands (Z) has a significant positive effect on purchase intention (Y) with a standardized beta value of 0.417 and a significance of 0.000. Meanwhile, the attitude variable towards brands has a significant effect on purchase intention. Further research can be carried out through comparing consumer attitudes towards advertisements on several media with wider reach and affordable costs, such as the internet and social media. Keywords: Television Advertising, Attitude Towards Advertising, Attitude Towards Brands, Buying Interest.